Elevated river discharge enhances the immigration of juvenile catadromous and amphidromous fishes into temperate coastal rivers. Issue 1 (14th March 2021) - Amtstaetter, Frank; Yen, Jian D.L.; Hale, Robin; Koster, Wayne; O'Connor, Justin; Stuart, Ivor; Tonkin, Zeb
Abstract: Anthropogenic alterations to river flow regimes threaten freshwater biodiversity globally, with potentially disproportionate impacts on species that rely on flow cues to trigger critical life history processes, such as migration for diadromous fishes. This study investigates the influence of river discharge on the abundance of juvenile fish moving into rivers by four temperate catadromous or amphidromous species (common galaxias Galaxias maculatus, spotted galaxias Galaxias truttaceus, climbing galaxias Galaxias brevipinnis and the threatened Australian grayling Prototroctes maraena ). Fyke netting or fishway trapping was used to catch juvenile fish moving from estuaries into freshwater in five coastal waterways in south‐eastern Australia during the spring migratory period. There was a positive relationship between the probability of high catch rates and mean discharge in September. We also found a positive relationship between discharge and the number of recruits captured 22–30 days later in a flow stressed system. In addition, day‐of‐year had a strong influence on catch rates, with the peak abundance of juveniles for three species most likely to occur midway through the sampling period (spotted galaxias in October, climbing galaxias in late October and Australian grayling in late October and early November). Our study shows that higher magnitudes of river discharge were associated with increased catches of juvenile catadromous and amphidromous fishes. With a limited supply of environmental water, environmental flows used to enhance immigration of these fishes may be best targeted to maintain small amounts of immigration into freshwater populations in waterways or years when discharges are low and stable. When there are natural, large discharge volumes, relatively large numbers of juvenile fish can be expected to enter coastal waterways and during these times environmental flows may not be required to promote immigration.